If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -1) + (13 + 13) = 90 Reorder the terms: (-1 + 6x) + (13 + 13) = 90 Remove parenthesis around (-1 + 6x) -1 + 6x + (13 + 13) = 90 Combine like terms: 13 + 13 = 26 -1 + 6x + (26) = 90 -1 + 6x + 26 = 90 Reorder the terms: -1 + 26 + 6x = 90 Combine like terms: -1 + 26 = 25 25 + 6x = 90 Solving 25 + 6x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + 6x = 90 + -25 Combine like terms: 25 + -25 = 0 0 + 6x = 90 + -25 6x = 90 + -25 Combine like terms: 90 + -25 = 65 6x = 65 Divide each side by '6'. x = 10.83333333 Simplifying x = 10.83333333
| 2x^2+8x-46=0 | | (7+m)+m=35 | | An=-5n-5 | | 6=m-39 | | 8x+20=6x+34 | | 2x^2-16+15=0 | | 15=5x+2y | | 4x+30+=5x+10 | | Z-17=-5 | | (6x-1)+(9+9)=90 | | 9(2x+3)=y | | -3y+5=-3y-9 | | 24+15x=50+2x | | 3x+15=4x+1 | | 5x-13=5x+6 | | -4v(v+6)=-16 | | a-2a=8 | | -8+x=-10 | | 16+(22+a)=16+(a+22) | | 11-a=11 | | 4x+30+5x+10= | | 2e+2=3e+2 | | 2x/3+2x=3x+15 | | 10x-20=10(x+1) | | 5=4(-5+x)+1+-2x | | 4cosx-1=1 | | 212=(x+22)11 | | 9y+2b+2y+b= | | 12=5y | | -8(1-2x)-4x=-8(x-4) | | 6+4(6+3x)=2-2(-4x-6) | | 10(z+4)-3(z-3)=2(z-2)+4(z-1) |